2004
DOI: 10.1111/j.0301-5661.2004.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics of participants in the oral health component of the Women's Interagency HIV Study

Abstract: Dental and periodontal variables showed little difference between HIV sero-positive and sero-negative women. Among sero-positive women, there were significant differences in coronal and root caries by AIDS diagnostic criteria, but no periodontal indicators by either AIDS diagnostic criteria or CD4 status, were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 36 publications
0
43
2
Order By: Relevance
“…Older studies (8, 9, 13) as well as more recent studies (6, 36, 38) have reported lower levels of periodontal disease in HIV+ patients, compared to the level of PD in our cohort. Reasons for this may be due to: 1) how authors defined periodontal disease, 2) the methodology used to collect periodontal data, 3) the distribution of patient characteristics within cohorts (especially immune and medication-related), and 4) the limited number of post-HAART era investigations on this topic.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Older studies (8, 9, 13) as well as more recent studies (6, 36, 38) have reported lower levels of periodontal disease in HIV+ patients, compared to the level of PD in our cohort. Reasons for this may be due to: 1) how authors defined periodontal disease, 2) the methodology used to collect periodontal data, 3) the distribution of patient characteristics within cohorts (especially immune and medication-related), and 4) the limited number of post-HAART era investigations on this topic.…”
Section: Discussioncontrasting
confidence: 38%
“…Reasons for this may be due to: 1) how authors defined periodontal disease, 2) the methodology used to collect periodontal data, 3) the distribution of patient characteristics within cohorts (especially immune and medication-related), and 4) the limited number of post-HAART era investigations on this topic. Some studies that found low levels of periodontal disease (6, 8, 9, 13, 38) used partial mouth examination techniques that are known to potentially underestimate PD (18) and have not, to our knowledge, been validated in an HIV-1 infected cohort.…”
Section: Discussionmentioning
confidence: 99%
“…They observed linear gingival erythema (LGE) and necrotizing ulcerative gingivitis (NUG) in patients comparable to our group B only but not the A nor C groups. They also reported that necrotizing ulcerative periodontitis (NUP) occurred with similar prevalence in groups A and B, but not in C. These studies support the suggestion that the use of antiretroviral therapy (ART) has modified the prevalence and course of periodontal disease in HIV-positive patients [12,13,35,36] with reduced incidence of periodontal damage [37-39]. …”
Section: Discussionmentioning
confidence: 69%
“…A great difference was observed in HIV patients, when salivary flow is reduced or lacking, which makes alterations in saliva an important cofactor in oral manifestations of disease [2].…”
mentioning
confidence: 99%